La estrategia regional de cambio climático de Centroamérica y los desafíos para la integración ambiental y la cooperación internacional - Artiga Colato, Raúl (Revista Española de Desarrollo y Cooperación, 2023)
This article shows the priority of the environmental agenda for the countries of SICA. Climate variability associated with climate change reflects the highly regional vulnerability and deepen the socio-environmental problems. The progressive climate-related extreme events are increasingly impacting the infrastructure and maintain strong pressure on public finances of the Central American economies, calling for more effective responses to environmental integration and international cooperation.